Workshop Desain Media Pembelajaran Berbasis Android dalam Menghadapi Implementasi Kurikulum Merdeka - Fauzi, Lalu Muhammad; Gazali, Muhammad; Hayati, Nila; Satriawan, Rody; Rahmawati, B. Fitri; Dewi, Gustianti (Universitas Islam Negeri Raden Intan Lampung, 2022)
The use of technology in the world of education is a must where digital technology is currently an important part in supporting teaching and learning activities. Professional teachers have the obligation to plan learning, carry out quality learning processes, as well as assess and evaluate learning outcomes, so to carry out these obligations the first step a teacher must take is to design all learning tools. To improve this, it is considered important to provide workshops or training on Android-based learning media design. The workshop was carried out for one full day with details of the provision of materials, practice of making electronic applications and mentoring of participants after the workshop activities were completed. With the aim of increasing teacher competence in designing and utilizing android-based learning media in the learning process in the classroom. The workshop will be held on Saturday, August 6, 2022 at SMAN 2 Selong. The results of the workshop illustrate that participants have been able to create android-based learning media applications.